JavaScript Access to DICOM Network and Objects in Web Browser. - Drnasin, Ivan; Grgić, Mislav; Gogić, Goran (Journal of Digital Imaging, 2017)
Digital imaging and communications in medicine (DICOM) 3.0 standard provides the baseline for the picture archiving and communication systems (PACS). The development of Internet and various communication media initiated demand for non-DICOM access to PACS systems. Ever-increasing utilization of the web browsers, laptops and handheld devices, as opposed to desktop applications and static organizational computers, lead to development of different web technologies. The DICOM standard officials accepted those subsequently as tools of alternative access. This paper provides an overview of the current state of development of the web access technology to the DICOM repositories. It presents a different approach of using HTML5 features of the web browsers through the JavaScript language and the WebSocket protocol by enabling real-time communication with DICOM repositories. JavaScript DICOM network library, DICOM to WebSocket proxy and a proof-of-concept web application that qualifies as a DICOM 3.0 device were developed.